The right to the freedom of peaceful assembly under the rule of law: convergence and mutual implementation (Bulletin of Kharkiv National University of Internal Affairs, 2025)
Human rights, freedoms and interests determine the content and direction of a democratic state, and are the content of social relations in a democratic civil society. Reflecting on the issues of positive and negative interference of the State, the State apparatus, State bodies, local self-government bodies in public relations regarding the use, exercise and restoration of the right to freedom of peaceful assembly, the question arises as to the impact of the fundamental principles of building and functioning of power in a democratic state on their organizational and practical activities. One of such principles is the principle of the rule of law, which, voluminous in its content and purpose, has a significant direct and indirect impact on both the organization of public power and the content of legal relations in society. Therefore, the purpose of this article is to analyze the principle of the rule of law and its impact on the use and exercise of the right to freedom of peaceful assembly and to identify feedback loops. The article examines the content of the principle of the rule of law, the right to freedom of peaceful assembly, and the presence of connections between the above-mentioned legal phenomena that affect the use and exercise of this human right. The opinion is expressed on the impact of such links and their convergence on the above-mentioned legal phenomena, as well as the interdependence and mutual conditionality of the rule of law and the use and exercise of the right to freedom of peaceful assembly, and their theoretical content. According to the results of the study, it is concluded that not only the principle of the rule of law has an impact on the use and exercise of the right to freedom of peaceful assembly, but also the aforementioned right has a significant impact on the formation of the content of the rule of law. The results obtained as a result of the scientific study are aimed at: 1) the enriching theoretical knowledge about the place and role of the principle of the rule of law in the actions of public administration entities in creating conditions for the use and exercise of the right to freedom of peaceful assembly; 2) the forming systemic ties of interaction and mutual influence of the principle of the rule of law and the right to freedom of peaceful assembly; 3) the development of a holistic system of equal use and freedom of exercise of the right to freedom of peaceful assembly, limitation of interference by subjects of state power and local self-government in the exercise of this right, limiting the latter to the scope of creating fair conditions for its exercise and legitimate grounds for restriction or prohibition; 4) the improvement of the system of national legislation in the field of use, exercise and restoration of the right to freedom of peaceful assembly, as well as regulation of the powers of state power and local self-government bodies.
Keywords: rule of law; right to freedom of peaceful assembly; operation of law; subjects of public administration; freedom; equality; justice; use; exercise of law.